P6.060 Patient or Provider Referral For Chlamydia - What is the Cost and is It Worth It? A Cost Comparison of Alternative Strategies. (13th July 2013) - Roberts, T; Mistry, H; Rossello-Roig, M; Rait, G; Dodds, J; Lanza, S; Estcourt, C S; Symonds, M; Cassell, J A
Abstract : Background: Partner notification (PN) is an essential element of STI control. Typically partner notification has been supported by specialist health advisors based in GUM clinics, but recently the role has been extended to community based Chlamydia screening officers (including primary care). We aimed to explore and compare costs of various approaches to PN for Chlamydia in different settings. Methods: We compared costs of being offered one of five approaches to partner notification from the health service perspective: Routine specialist clinic PN (patient referral including infection specific information, and advice that the sex partner should attend clinic for testing and treatment) Accelerated Partner Therapy (APT Hotline): nurse initiated PN at the general practise followed by telephone assessment of sex partner by clinic-based nurse qualified health adviser; Accelerated Partner Therapy (APT Pharmacy): nurse initiated PN at the general practise followed by assessment of sex partner by trained community pharmacist; Patient referral, where patients are advised by phone by qualified health adviser on the need for partner to be tested and treated. Provider referral, where patients accept the offer of a specialist health adviser contacting one or more partner(s) by phone. For all pathways primary costs were collected prospectively in a specific exploratory study. Results: The least costly strategy is nurse led PN (strategy 2) costing approximately £53 per index case (2011 costs). The most costly strategy is provider referral (strategy 6) which cost £96 per index case. Conclusion: Where health service providers assume responsibility for contacting partners there will be substantial additional cost. Before any such policy is implemented, a demonstrable improvement in PN outcomes should be established.